Value relevance of group versus holding company financial statements with application of fair value option under IAS 39: a Malaysian context - Ching Sien, Fu (2014)
The value relevance of group and holding company financial statements has long been debatable. Various studies have been conducted in order to examine the usefulness of the financial statements, particularly by comparing the group and holding financial information, in order for investors to evaluate the business performance. With the adoption of International Accounting Standard (IAS) 39: Financial Instruments: Recognition and Measurement, this study is set to evaluate the value relevance of financial reporting in Malaysia. With the sample of top 100 companies listed on Malaysia bourse – Bursa Malaysia (the constituents of FBMT100 Index), this study compiles and compare the data in terms of Group and Holding, as well as Pre IAS 39 and Post IAS 39 adoption. With an adopted price model based on Ohlson (1995), the overall outcome is consistent with many studies, which conclude the group financial information is more value relevant than the holding company financial information, regardless pre or post IAS 39. However, it is slightly beyond expectation that the Finance industry shows a completely opposite result as compared to Non-Finance industry, where the Post IAS 39 financial information of Finance company shows greater explanatory power than Pre IAS 39. This indicates that IAS 39 has resulted in higher value relevance level among Finance stocks, while its practicability for Non-Finance stocks is deemed to be improved. With another major revamp from IAS 39 to IFRS 9: Financial Instruments, which is set to be effective for annual periods beginning on or after 1 January 2015 (where IAS 39 will be superseded by IFRS 9), it is expected that the enhanced standard will improve the quality of financial reporting in terms of value relevance of financial reporting in Malaysia.